Development of National Identity and The Pride of Students in The Educational Process - Ruzieva, Dilnoz Isamjanovna (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of scientifically substantiating the development of national self-awareness and the pride of students in the educational process. The following tasks are defined in the article: to reveal the essence, content, basic structural components of the national self-awareness and pride of the student’s personality, to determine their relationship; to develop a pedagogical model for the effective formation of national self-awareness and pride of students; identify and justify pedagogical conditions that ensure the optimality of the process of formation of national self-awareness and pride of students in the context of a national idea and the basis of spirituality.